The Relationship Between Medication Compliance and Blood Pressure in Hypertensive Elderly at Limboto Health Center - Rindiani Yulia Safitri Ahmad; Zuhriana K. Yusuf; Nur Ayun R. Yusuf (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Hypertension is a condition when arterial blood pressure rises steadily above normal limits and lasts for a long time. The high prevalence of hypertension is still caused by the low compliance of hypertensive patients in taking antihypertensive drugs. This study aims to determine the relationship between medication adherence to medication and blood pressure in hypertensive elderly at Limboto Health Center. This research is a type of quantitative research with a cross sectional approach. The population in this study is 246 elderly hypertensive patients registered at Prolanis at the Limboto Health Center. The research sample amounted to 38 hypertensive elderly people who were taken using a non-probability sampling technique with an accidental sampling approach. The research instrument used the Morisky Medication Adherence Scale (MMAS-8) questionnaire to measure the level of adherence to taking medication. The data analysis used was the Chi-Square test. The results showed a p value of 0.002 (p < 0.05), which means that there is a significant relationship between medication adherence to blood pressure in hypertensive elderly people. This research is expected to be the basis for the health center in improving health education, monitoring medication adherence regularly, and involving families in treatment supervision so that blood pressure control in the elderly can be achieved optimally and sustainably.